Peningkatan Penguasaan Materi Melalui Model Learning Cycle 5E Berbantuan Video Pembelajaran - Masbait, Kristi Wansia; Huliselan, Estevanus Kristian; Tamaela, Elsina Sarah (Pattimura University, 2025)
The purpose of this study is to find out how well eighth-grade students at SMP Negeri 39 Central Maluku learn vibration and wave topics when they are taught using the Learning Cycle 5E model and learning videos. The research design used was a one-group pretest-posttest, with 16 students used as research subjects. The instruments used in collecting data for this study consisted of test instruments in the form of test questions and non-tests in the form of Learner Worksheets (LKPD). The study's results indicate that the material mastery ability of all students (100%) falls into the failing qualification category, with an average score of 20.54. The analysis reveals that students achieve an average score of 78,60 during the learning process, indicating a good qualification. The results of the N-Gain Test show that the average score of students is 0.70, which is a high qualification. The results showed that there was an increase in students' mastery of material in each indicator of competency achievement, with an average final score of 75.71. This means that using the Learning Cycle 5E model along with learning videos has been shown to help all of the students at SMP Negeri 39 Central Maluku learn more about vibration and waves.